HUBUNGAN SELF-EFFICACY DAN MANAJEMEN DIRI PENDERITA DM TIPE 2 PADA MASA PANDEMI COVID-19 - rahmadiya, Siska (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Introduction : Diabetes mellitus type 2 is a metabolic condition brought on by either the body's ineffective use of insulin or diminished insulin synthesis by pancreatic ß-cells called hyperglycemia. People with Type 2 Diabetes Mellitus can self-manage their high blood sugar.  During the COVID-19 epidemic, Type 2 Diabetes Mellitus patients had trouble managing their condition on their own. The CoVID-19 pandemic has caused everyone's activities to be limited. People with diabetes mellitus saw a decline in their capacity to do self-care during the Covid-19 epidemic. This study was conducted to determine the relationship between self-efficacy and self-management of people with Type 2 DM during the COVID-19 pandemic.. Methods: This study's cross-sectional methodology approach and correlational research design involved 88 respondents. Result: The study's findings revealed that 58 participants (92.1%) had sufficient self-efficacy and 17 respondents (68.0%) had very confident self-efficacy. The Chi-Square test's statistical findings revealed a significant relationship between self-efficacy (p-value (0.007)) Conclusions : In order to maximize self-management during a pandemic or post-pandemic, researchers believe that nursing services will be able to evaluate the elements that affect the self-management of persons with Type 2 DM. Key words: Type 2 DM, Self Management, COVID-19 pandemic, Self Efficacy